Spatio-temporal mutation profiles of case-matched colorectal carcinomas and their metastases reveal unique de novo mutations in metachronous lung metastases by targeted next generation sequencing. Issue 1 (December 2016) - Kovaleva, Valentina; Geissler, Anna-Lena; Lutz, Lisa; Fritsch, Ralph; Makowiec, Frank; Wiesemann, Sebastian; Hopt, Ulrich; Passlick, Bernward; Werner, Martin; Lassmann, Silke
Abstract Background Targeted next generation sequencing (tNGS) has become part of molecular pathology diagnostics for determining RAS mutation status in colorectal cancer (CRC) patients as predictive tool for decision on EGFR-targeted therapy. Here, we investigated mutation profiles of case-matched tissue specimens throughout the disease course of CRC, to further specify RAS-status dynamics and to identifyde novo mutations associated with distant metastases. Methods Case-matched formalin-fixed and paraffin-embedded (FFPE) resection specimens (n = 70; primary tumours, synchronous and/or metachronous liver and/or lung metastases) of 14 CRC cases were subjected to microdissection of normal colonic epithelial, primary and metastatic tumour cells, their DNA extraction and an adapted library protocol for limited DNA using the 48 gene TruSeq Amplicon Cancer PanelTM, MiSeq sequencing and data analyses (Illumina). Results By tNGS primary tumours were RAS wildtype in 5/14 and mutated in 9/14 (8/9KRAS exon 2; 1/9NRAS Exon 3) of cases. RAS mutation status was maintained in case-matched metastases throughout the disease course, albeit with altered allele frequencies. Case-matched analyses further identified a maximum of three sequence variants (mainly inAPC, KRAS, NRAS, TP53 ) shared by all tumour specimens throughout the disease course per individual case. In addition, further case-matchedde novo mutations were detected in synchronous and/or metachronous liver and/or lung metastases (e.g. inAPC, ATM, FBXW7, FGFR3, GNAQ, KIT, PIK3CA, PTEN, SMAD4, SMO, STK11, TP53, VHL ). Moreover, severalde novo mutations were more frequent in synchronous (e.g.ATM, KIT, PIK3CA, SMAD4 ) or metachronous (e.g.FBXW7, SMO, STK11 ) lung metastases. Finally, somede novo mutations occurred only in metachronous lung metastases (CDKN2A, FGFR2, GNAS, JAK3, SRC ). Conclusion Together, this study employs an adapted FFPE-based tNGS approach to confirm conservation of RAS mutation status in primary and metastatic tissue specimens of CRC patients. Moreover, it identifies genes preferentially mutatedde novo in late disease stages of metachronous CRC lung metastases, several of which might be actionable by targeted therapies.